Perception of adolescent mothers regarding the use of contraceptive methods in communities annexed in jungle region, 2018 - Coronado-Quispe, Joel (2021)
Introduction: The Peruvian jungle is a geographical area with a high birth rate, and it has the highest proportion of teenage mothers; DHS revealed that only 28.4% of teenage women in the country have ever used contraception. Objective: To identify the perception of adolescent mothers regarding the use of contraceptive methods in communities annexed to the district of Masisea-Ucayali in 2018. Materials and Methods: Qualitative study of the “Phenomenological" type The population studied was made up of adolescent mothers between 12-19 years of age. A sample of 13 people was obtained by means of a qualitative theoretical sampling. A constant comparative analysis was used to analyze and draw conclusions from the interview data. Results: Most of the women participating in the study have basic knowledge about contraceptive methods; on the other hand, their perspective on these methods is influenced by various factors. One of the most relevant factors in the perception is the experience of the participants regarding the side effects of contraceptives, especially hormonal ones; a second relevant factor is the opinion of the couple regarding their use, since 100% of the women with a partner referred to consult their partner before using any contraceptive. Conclusions: Our study concludes that the perspective of the participants is influenced by the socio-cultural context; likewise, the local health center is recognized as the main disseminator of information regarding contraceptive methods.